Pengaruh Proporsi Terigu dan Tepung Sukun (Artocarpus altilis) Terhadap Karakteristik Brownis Panggang - Singarsari Diasaputri, Ketut Ayurina; Puspawati, Ni Nyoman; Suparthana, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i04.p25, 2023)
Brownies is a soft textured cake with a distinctive chocolate flavor. This study aims to determine the effect of adding breadfruit flour on the characteristics of brownies and determine the right proportion of breadfruit flour to produce brownies with the best characteristics. The experimental design used in this study was a completely randomized design (CRD) with the addition of breadfruit flour consisting of 6 treatment levels: 0%, 5%, 10%, 15%, 20% and 25%. Each treatment was repeated 3 times to obtain 18 experimental units. Data were analyzed using variance and in the treatment which showed a significant effect followed by the Duncan Multiple Range Test (DMRT). The results showed that the addition of breadfruit flour had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, hedonic tests (color, texture, taste and aroma) and scoring tests (texture and taste). The addition of breadfruit flour as much as 15% produces the best product with the characteristics of a moisture content of 17.19%, ash content of 1.55%, protein content of 4.46%, fat content of 27.40%, carbohydrate content of 49.38%, crude fiber content of 8 .50%, preferred color, preferred soft texture, preferred brownie distinctive taste, preferred aroma and preferred overall acceptability.